Predictors of the development of communicative behavior of schoolchildren adolescence (Actual Problems of Psychology in Educational Institutions, 2023)
The article is devoted to the analysis of the comprehensiveproblem of the development of communicative behavior of schoolchildrenof adolescent and youth age. The characteristics of the sociolect ofmodern youth are considered. The scientific argumentation of the necessarypolymodality of the study of sociocultural predictors of the developmentof communicative strategies of the behavior of adolescents and youth inthe dialogic educational space is presented. The results of the empiricalmeasurement of the communication direction of teenagers and young menare presented. It was established that the orientation of schoolchildrenin the period of adulthood in the coordinates “I — Other” has a mainlymonologic vector. It has been statistically confirmed that the differencesin the detection of personality orientation in communication betweenschoolchildren studying in secondary education institutions of differenttypes are statistically insignificant, these characteristics in the comparedgroups differ only quantitatively. It is emphasized that the results ofthe empirical study indicate the insufficiency of purposeful influencein educational institutions regarding the development of a variablecommunicative dialogic culture of schoolchildren and a dialogic modelof professional interaction in the “Teacher — Student” system withoutdisturbing the professional-communicative balance. It is noted that theintroduction of a dialogue system in education is an essential factor in thedevelopment of the personal potential of each participant in the educationalprocess.
Keywords: communicative behavior; sociolect; dialogue; pedagogical communication; personal potential; personal autonomy; adolescence and youth; educational space; tolerance to uncertainty; professional-communicative balance